If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1 + 9 = 3x + -6 Reorder the terms: -1 + 9 + X = 3x + -6 Combine like terms: -1 + 9 = 8 8 + X = 3x + -6 Reorder the terms: 8 + X = -6 + 3x Solving 8 + X = -6 + 3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + X = -6 + -8 + 3x Combine like terms: 8 + -8 = 0 0 + X = -6 + -8 + 3x X = -6 + -8 + 3x Combine like terms: -6 + -8 = -14 X = -14 + 3x Simplifying X = -14 + 3x
| 1.45^1/2 | | F(t)=(1.45)^t/2 | | -3.7x=12.4 | | -26+9+y=-2+11 | | 7=4-a | | 8x+62=10+x+5 | | 4(4-d)-26=26d-5(2+6d) | | -12=4(x-8)+32 | | x^(17/3) | | 36=15c | | 22-3x=-4(4x+2)-4(-3-3x) | | X=-5b+12 | | 8(x+62)=10(x+5) | | 29-(-5)=-2x+13-x | | 4+6x=3(2x+3) | | x-(6+3x)= | | 2x+2+2x+2= | | -7+(9x+2)=-(6x+3)-9 | | 5m+5=-100 | | 15x=2x^2+28 | | 2x+64.2=90 | | X=4(59/13)-20 | | 3y+21=3y-6 | | y=5lny | | -6y-5(-3y-5)=8-7(1-y) | | 3logx(5)+logx(3)=7 | | 11-3x=5x+8-7x | | 14x+69=0 | | 0.3(x+40)-0.06(x-60)=6 | | 5(2-d)=6(d-5)+6d | | 8(-2-7)=28+5x | | -20.5=w/6-1.3 |